2014
DOI: 10.1177/2158244014538270
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Quality of Ecotourism Services

Abstract: Ecotourism forms the pillar of the country's tourism industry. Ecotourists make up more than 10% of international tourists in Malaysia. When service quality is thought of as an important factor to the success of tourism service providers, the importance of estimating service quality provided to tourists becomes apparent. Estimating service quality provides tourism service providers with the necessary information needed to manage their marketing operations appropriately. Therefore, this estimation should be per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 46 publications
(61 reference statements)
0
26
0
5
Order By: Relevance
“…Although cruise tourism is among the tourism phenomena that are experiencing significant growth [1], it has not received much attention from an academic point of view [13,14], especially in terms of cruisers' service quality perceptions. This is worrying, since service quality studies can assess how successful service ambassadors fulfill tourists' needs according to tourists' perceptions, helping cruise ship staff to prioritize tourists' needs, wants, and expectations [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although cruise tourism is among the tourism phenomena that are experiencing significant growth [1], it has not received much attention from an academic point of view [13,14], especially in terms of cruisers' service quality perceptions. This is worrying, since service quality studies can assess how successful service ambassadors fulfill tourists' needs according to tourists' perceptions, helping cruise ship staff to prioritize tourists' needs, wants, and expectations [15].…”
Section: Introductionmentioning
confidence: 99%
“…They are as follows: personnel response, complementary offer, tourist relations, tangible elements, and empathy. Yusof et al, (2014) developed that a scale comprising seven dimensions to measure the service quality expectations and perception of Eco-tourists in lodging on ecotourism destination. They are as follows: sustainability, sustainable practices, tangibility, reliability, responsiveness, assurance, and empathy.…”
Section: Perceived Service Qualitymentioning
confidence: 99%
“…This research found that the height was ecotangibles. Yusof et al, (2014) study showed that a scale comprising seven dimensions to measure the service quality expectations and perception of Eco-tourists in lodging on ecotourism destination. They are as follows: sustainability (visual attraction and the appeal of natural attractions), sustainable practices (development integrated with local environment/ culture), tangibility, (physical facilities and natural resources), reliability (the staff provides on-time services), responsiveness (the staff is willing to assist tourists), assurance (the staff has the knowledge that is necessary to answer questions) and empathy (the staff understands the specific needs of tourists).…”
Section: Dimension Of Services Quality Scale In Traditional Hotel Andmentioning
confidence: 99%
“…In this study, the researcher conducted the hotel and Eco lodge model from the previous research of service quality to develop ECO-SERQUAL model to measure the perceived quality of ecoguest in Egyptian ECO-lodge context. The process of developing the scale goes through four stages: The first stage explores the service quality model in general industry, hotel industry, and eco-lodge context and the researcher found that there are two original scales applied in general industry SERVQUAL (Parasuraman, et al, 1985(Parasuraman, et al, , 1988 and SERVPERF (Cronin andTaylor 1992, 1994 ), In addition, there are ten developed model used to evaluated service quality in traditional hotel and eco lodge depend on the original scale that are fellow: ECOPERF (Ban and Ramsaran, 2016), HOTPERF (Tefera and Govender, 2014) ECOSERV (Yusof et al, 2014), MECOSER (Said et al, 2013), ECOCOM (Bastic and Gojcic, 2012), RE (Saez et al, 2007), ECOSER (Khan, 2003), LOI (Getty and Gettz, 2003), HOLSERV (Wong et al, 1999), LODSERV (Stevens et al, 1990). The second stage comprising between the general scale, hotel and eco-lodge model in order to identify names of different dimensions of the scale developed for hotel industry in general and ecolodge in particular and determined number of frequencies dimensions are repeated in each scale separately for inference dimensions names of proposed scale in this study.…”
Section: Eco-servqual Scale Development Stagesmentioning
confidence: 99%